"Crowding out effects of government spending": a comment - Fagan, Gabriel; Barry, Frank; Devereux, Michael B. (Economic & Social Studies, 1992)
This paper presents a review of the current state of macroeconomic theory concerning the impact of Government spending on economic activity. The models presented reflect the current approach in theoretical analysis of economic activity, incorporating such features as: A general, rather than partial, equilibrium approach to model building; Agents' behaviour is modelled as the result of the solution of an optimisation problem - maximising utility or profits. This contrasts with earlier approaches in which, in many cases, the postulated behaviour of agents was not derived as a solution to an optimisation problem (e.g., the Keynesian consumption function); The models are set in an intertemporal framework rather than the static approach previously employed; Expectations are assumed to be rational instead of the assumption of static or adaptive expectations previously employed; The impact of market clearing or non-clearing is explicitly accounted for.
Keywords: Government spending; Fiscal policy; Macroeconomics